Boosting Synergistic Effects of Short Antimicrobial Peptides With Conventional Antibiotics Against Resistant Bacteria - Wu, Chih-Lung; Peng, Kuang-Li; Yip, Bak-Sau; Chih, Ya-Han; Cheng, Jya-Wei (Frontiers in Microbiology, 2021)
Due to the global spread of antibiotic-resistant bacterial and fungal strains, there is an urgent need to develop new antimicrobial alternatives. In this study, we describe a method to boost antibacterial activities and synergistic effects with conventional antibiotics of short antimicrobial peptides by adding the non-nature bulky amino acid β-naphthylalanine to their termini. A checkboard method was used to evaluate synergistic effects of the peptides. Moreover, boron-dipyrro-methene (BODIPY) labeled vancomycin was used to characterize the synergistic mechanism of action between the peptides and vancomycin on the bacterial strains. Attenuation of the antibiotic-induced release of LPS from E. coli by the peptides was also found. Our results demonstrate that β-naphthylalanine end-tags could help in developing antimicrobial peptides that not only have enhanced antibacterial activities but also increase the synergistic effects with conventional antibiotics against antibiotic-resistant bacteria.